CHA2DS2-VASc score as a mortality predictor in acute heart failure with preserved ejection fraction - Kądzioła, Olaf; Stępień, Konrad; del Carmen Yika, Alicia; Kurek, Maria; Kachnic, Natalia; Karcińska, Aleksandra; Platschek, Michael; Wyleciał, Zuzanna; Nowak, Karol; Siniarski, Aleksander; Nessler, Jadwiga (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe mortality rate in decompensated heart failure (HF) with preserved ejection fraction (HFpEF) remains high. In recent years the prognostic role of CHA2DS2-VASc score, initially formulated for embolic risk prediction in atrial fibrillation, has been shown in other diseases including HF. We sought to analyze a long-term mortality in decompensated HFpEF patients depending on CHA2DS2-VASc score.Methods261 (22.74%) out of 1,148 patients included in the single-center Lesser Poland Cracovian Heart Failure (LECRA-HF) Registry between 2009 and 2022 were diagnosed with decompensated HFpEF. We identified 213 (81.61%) subjects with CHA₂DS₂-VASc score ≥4 points and 48 (18.39%) < 4 points.ResultsPatients with CHA₂DS₂-VASc ≥4 were older (79 vs. 64 years, P < 0.001), mostly females (65.3% vs. 27.1%, P < 0.001), and were characterized by atrial fibrillation (62.9% vs. 31.3%, P < 0.001), prior myocardial infarction (24.4% vs. 6.3%, P = 0.005), percutaneous coronary intervention (23.0% vs. 4.2%, P = 0.003) and coronary artery bypass surgery (11.3% vs. 2.1%, P = 0.049) compared to CHA2DS2-VASc <4 cohort. Lower baseline GFR (by 26.7%, P < 0.001), potassium (by 4.4%, P = 0.02), hemoglobin (by 10.3%, P < 0.001), as well as hematocrit (by 8.1%, P = 0.003) were noted in CHA2DS2-VASc ≥4 patients. In a long-term follow-up (median 4.3 years), overall mortality was significantly higher in CHA2DS2-VASc ≥4 group (P = 0.005) and CHA2DS2-VASc ≥4 was its independent predictor (HR 3.54, 95% confidence interval 1.68–7.49). In a multivariable Cox regression analysis, each one-point increase in CHA2DS2-VASc score raised all-cause mortality risk by 32%.ConclusionsAs has been shown for the first time CHA2DS2-VASc score was an independent prognostic parameter in decompensated HFpEF.